PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH DAN MOTIVASI BELAJAR DENGAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION - Romli, - (2014)
Problem solving ability and learning motivation of student at math is a component that has an important role in building students' mathematical power. Therefore, to build this ability, teacher as an actor in the class must be able to create meaningful learning for students, one of which is to find the right strategy or method to problem-solving ability and learning motivation of student can be explored properly. This study aimed to determining whether the Realistic Mathematics Education (RME) approach can enhance problem solving ability for student in mathematics as well as to determining whether the RME approach could affect to learning motivation for student in mathematics. This study is a quasi experimental study with a pretest posttest control group research design. The population in this study were students of class VA and VB in SDN Karyawangi 1 PulosariPandeglang District of Banten Province. Data collected by the test form of description, student motivation questionnaire, attitude scale questionnaire and interviews. For data processing used SPSS 13. Based on data analysis scores posttest and data normalized gain, it can be concluded that the mathematical problem-solving ability of students who receiving learning with RME approach more increased than the problem-solving ability of students who use learning conventional, there is a significant effect on the students' learning motivation treated with the implementing RME approach teaching, as well as students' response to the application of learning RME provide high response, with the application of RME learning makes students motivated to learn. Based on the findings, the study of mathematics by RME approach can be used as an alternative approach to teaching mathematics that can be applied in an effort to improve math problem solving ability and learning motivation of students, the author also recommends further research to test the RME approach on other variables.